2017
DOI: 10.1080/00207454.2017.1308930
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a computer-based cognitive training program in older people with subjective memory complaints: a randomized study

Abstract: Our findings suggested that cognitive training of moderate intensity, supported by a web platform, could lead to significant improvements in cognitive and psychological well-being in older people with subjective memory complaints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
87
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(91 citation statements)
references
References 54 publications
1
87
1
1
Order By: Relevance
“…Of the 20 included studies, five were classified as psychological interventions—four as group psychological treatment 28–31 and one as mindfulness training. 32 Eleven studies were classified as cognitive or memory training, 28 33–42 two as lifestyle 35 43 and four as pharmacological 44–47 interventions. Three studies 31 33 46 examined two differing interventions from the same category while two studies investigated interventions from different categories.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 20 included studies, five were classified as psychological interventions—four as group psychological treatment 28–31 and one as mindfulness training. 32 Eleven studies were classified as cognitive or memory training, 28 33–42 two as lifestyle 35 43 and four as pharmacological 44–47 interventions. Three studies 31 33 46 examined two differing interventions from the same category while two studies investigated interventions from different categories.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies 31 33 46 examined two differing interventions from the same category while two studies investigated interventions from different categories. 28 35 …”
Section: Resultsmentioning
confidence: 99%
“…However, there are very few studies of older Mexicans adults that have discussed whether the improvement of cognitive functions can have short or long-term effects with the use of technology. The studies mentioned above have found that cognitive interventions based on ICT can result in improvements in many perceptual and cognitive abilities [27-35]. Thus, these types of interventions are potentially an ideal solution to address the many perceptual and cognitive declines associated with aging.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these types of interventions are potentially an ideal solution to address the many perceptual and cognitive declines associated with aging. The study by Pereira-Morales et al [35] suggested that cognitive training of moderate intensity, supported by a web platform, could lead to significant improvements in cognitive and psychological well-being in older people with subjective memory complaints. Shellington et al [30] argue that sixty percent found the app was easy to use or similar to what they experienced with square-stepping exercise in the laboratory setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation